Models of electronic supervision system in Polish penal executive law - Baran, Beata (Актуальні проблеми правознавства, 2018)
One of the most important and modern solutions implemented into the Polish penal executive law system is the electronic supervision. In this paper the history of its implementation will be discussed as well as the current position in legal system.